2006
DOI: 10.1002/eji.200535402
|View full text |Cite
|
Sign up to set email alerts
|

Expression and alternative processing of IL‐18 inhuman neutrophils

Abstract: Interleukin-18 (IL-18), a member of the IL-1 cytokine superfamily, is an important regulator of both innate and acquired immune responses. We demonstrate here constitutive expression of IL-18 by human neutrophils. Unexpectedly, we observed that neutrophils from peripheral blood or rheumatoid synovial compartments contained not only pro and mature IL-18, but also several novel smaller-molecular-weight IL-18-derived species. Using specific protease inhibitors, and serine protease gene-targeted mice, we demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(52 citation statements)
references
References 56 publications
3
48
0
1
Order By: Relevance
“…These experiments suggest that overnight cultures of TLR-stimulated PMNs may contain species of IL-18 that are not detected by the ELISA, which is in line with previous reports demonstrating that neutrophil-derived proteases generate low m.w. species of IL-18 (23). To address this issue, we exposed rIL-18 to the neutrophil enzyme, elastase.…”
Section: Neutrophil Conditioning Of Nk Cells Is Caspase Dependent Andmentioning
confidence: 99%
“…These experiments suggest that overnight cultures of TLR-stimulated PMNs may contain species of IL-18 that are not detected by the ELISA, which is in line with previous reports demonstrating that neutrophil-derived proteases generate low m.w. species of IL-18 (23). To address this issue, we exposed rIL-18 to the neutrophil enzyme, elastase.…”
Section: Neutrophil Conditioning Of Nk Cells Is Caspase Dependent Andmentioning
confidence: 99%
“…However, stimulation of epithelial cells with IFN-γ in the presence of PR3 and lipopolysaccharide (LPS) leads to the release of biologically active mature IL-18, independent of caspase 1 (Sugawara et al, 2001). In contrast, it has been shown that mature IL-18 released by neutrophils can be proteolysed by NE leading to diminished biological activity (Robertson et al, 2006).…”
Section: Neutrophil Serine Proteases In the Modulation Of Chemokines mentioning
confidence: 99%
“…IL-18, a proinflammatory cytokine, belongs to the IL-1 cytokine superfamily and is synthesized as a precursor protein (pro-IL-18). In the presence of IL-1β-converting enzyme (ICE, or caspase-1), the precursor protein matures into an 18-kDa active protein (22), which is produced by macrophages, dendritic cells, neutrophils and epithelial cells (22,23). Neutrophils constitutively produce both IL-18 and its antagonist, IL-18 BP (24).…”
Section: Interleukin-18 Delays Neutrophil Apoptosis Following Alcoholmentioning
confidence: 99%